Mineral composition of raw and marinated-cooked arms from Pacific giant squid (Dosidicus gigas). - Fernández, Faustina; Bañón, Celia Lucas and Sancho (Emirates Journal of Food and Agriculture, 2021)
Background/aim: Shellfish consumption is often perceived as a potential health hazard due to the accumulation of toxic metals. The mineral content was investigated in marinated-cooked giant squid (Dosidicus gigas) arms from three Eastern Pacific fisheries (Peru, Chile and Benthic) to elucidate their contribution to daily recommended intakes and possible presence of pollutants. Material and methods: Thirty macro- and microminerals were analysed in the raw material, marination solution, cooking broth and cooked product. Results: Both raw and marinated-cooked squid arms contained nutritionally relevant quantities of essential macro- (Na and Mg) and microminerals (Cr, Zn, Mn and Se). Fishery origin led to minor variations in the mineral composition of raw arms, while marinated-cooked arms of Benthic origin had a higher retention of Na and juice likely due to their greater size. Levels of Pb, Hg, Zn or As found in the ready-to-eat product were below tolerable upper intake levels. Conclusion: The mineral content found in the raw squid arms suggests that the Pacific fisheries concerned are not affected by human polluting activities. Marinated-cooked squid arms cover a part of the dietary requirements for minerals and can be consumed without apparent negative nutritional implications.